Pembuatan Waterflow Otomatis Untuk Mempermudah Pengairan Rumah Pangan - Sarhan; Rahman, Asriezza Geuthena; Manurung, Rudiando; Annur, Shofiyah Nabila; Prameswari, Nadine; Amalia , Nindy Putri; Farahdina, Rima; Humairah, Rifa Khalisha; Putri, Gabrielle Havana; Arini, Fadhilah Sukma; Yustina (Yayasan Kajian Riset Dan Pengembangan Radisi, 2024)
One of the adaptation efforts in the Climate Village Program (PROKLIM) is food security and controlling plant development to be more effective. Beringin Indah Complex has village potential in the form of plants dominated by several plants such as Brazilian spinach and sweet potatoes which are good for health benefits. However, there are complaints from partners regarding the treatment of plants with watering media to solve this problem, so waterflow is made. This waterflow is made to make it easier for KWT members to care for plants. The initial activity is the collection and consideration of waterflow with drilled wells using Arduino pumps and sensors. Various considerations in the installation of drilled wells such as operational costs, maintenance costs, installation costs, security and control systems are obstacles. Because of this, the installation of waterflow flow was not realized as planned, so the second plan was realized by taking water sources from the house of the chairman of KWT and making flows to food houses using pipe installation methods that were in accordance with the scheme connected with elbow, tee and pipe glue. Monitoring the comparison of plant growth quality before and after waterflow. Achieving the target, with the construction of this waterflow, the development of plants becomes better so that KWT can produce plants in terms of quantity and quality appearance so that KWT products can be consumed and compete in the market world. Keywords: Waterflow, Arduino, Society